Fabrication and High-Resolution Structural Characterisation of 2D Material Moiré Structures - Ljungberg, Eric (My University, 2026)
Atomically thin two dimensional (2D) materials have become a major research topic since the discovery of graphene. In particular, 2D transition metal dichalcogenides (TMDs), such as MoS2, have attracted extensive research interest due to their unique electrical and optical properties suited for a future-generation of electronic and optical devices. One unique property of 2D materials is that atomically thin layers can be artificially stacked together building tunable structures, for example, Moiré structures. Moiré structures constructed by atomically thin TMDs can be designed to generate and control new material properties, including superconductivity, ferroelectricity, and quantum hall effect. Understanding the fabrication of 2D TMD Moiré structures by stacking atomically thin layers, and determining the structure of 2D TMD Moiré structures with high spatial resolution, are of critical importance for developing and using the novel structures of 2D materials. In this thesis work, an experimental setup and protocol for fabricating twisted TMD Moiré structures were successfully developed and completed. The fabrication procedure involves the preparation of atomically thin TMD layers from bulk crystals, accurate determination of thicknesses, and mechanical stacking of individual 2D TMD layers in a controllable manner. Then, the structure of twisted TMD Moiré structures was characterized at the nanometre and atomic scales using transmission electron microscopy (TEM) and scanning TEM (STEM). The focus was on stacked bilayer-bilayer and monolayer-monolayer MoS2 Moiré structures. Electron diffraction and TEM dark field (DF) imaging were used to reveal nanoscale domain structures resulting from atomic reconstruction in the Moiré structures. Moiré structures with parallel and anti-parallel stacking showed distinctly different domain structures. Furthermore, STEM imaging provided a direct visualization of domain and domain boundary structures at the atomic scale. DFT calculations were used to propose an hypothesis for the possible atomic arrangement at the Moiré domain boundaries. Possible electrical polarization resulting from changes in the atomic stacking of the structures was also studied using TEM selected area electron diffraction patterns. Evidence of in-plane polarization in MoS2 Moiré structures was observed in electron diffraction, while out-of-plane polarization in MoS2 with rhombohedral stacking was investigated using differential phase Contrast (DPC) STEM imaging.
Keywords: 2D Materials; TMD; DPC; STEM; TEM; Twist-tronics; Moiré Structures; Atomic Resolution Imaging